Trans, trans-farnesol as a mevalonate-derived inducer of murine 3T3-F442A pre-adipocyte differentiation - Torabi, Sheida (Exp Biol Med (Maywood), 2015)
Based on our finding that depletion of mevalonate-derived metabolites inhibits adipocyte differentiation, we hypothesize that trans, trans-farnesol (farnesol), a mevalonate-derived sesquiterpene, induces adipocyte differentiation. Farnesol dose-dependently (25–75 μmol/L) increased intracellular triglyceride content of murine 3T3-F442A pre-adipocytes measured by AdipoRed™ Assay and Oil Red-O staining. Concomitantly, farnesol dose-dependently increased glucose uptake and glucose transport protein 4 (GLUT4) expression without affecting cell viability. Furthermore, quantitative real-time polymerase chain reaction and Western blot showed that farnesol increased the mRNA and protein levels of peroxisome proliferator-activated receptor γ (PPARγ), a key regulator of adipocyte differentiation, and the mRNA levels of PPARγ-regulated fatty acid-binding protein 4 and adiponectin; in contrast, farnesol downregulated Pref-1 gene, a marker of pre-adipocytes. GW9662 (10 µmol/L), an antagonist of PPARγ, reversed the effects of farnesol on cellular lipid content, suggesting that PPARγ signaling pathway may mediate the farnesol effect. Farnesol (25–75 μmol/L) did not affect the mRNA level of 3-hydroxy-3-methylglutaryl coenzyme A reductase, the rate-limiting enzyme in the mevalonate pathway. Farnesol may be the mevalonate-derived inducer of adipocyte differentiation and potentially an insulin sensitizer via activation of PPARγ and upregulation of glucose uptake.